Integration through Hysteresis: SACU in a Comparative and Contextual Perspective - (:unkn) unknown (My University, 2005)
Actes de : "The new SACU Agreement in a Comparative Perspective", Annual conference on Monitoring regional integration in Southern Africa, NEPRU/Konrad Adenauer Stiftung, Windhoek (Namibie), 11-12 June 2005
Keywords: African Research